Firing Properties of Genetically Identified Dorsal Raphe Serotonergic Neurons in Brain Slices - Mlinar, Boris; Montalbano, Alberto; Piszczek, Lukasz; Gross, Cornelius; Corradetti, Renato (Frontiers in Cellular Neuroscience, 2016)
Tonic spiking of serotonergic neurons establishes serotonin levels in the brain. Since the first observations, slow regular spiking has been considered as a defining feature of serotonergic neurons. Recent studies, however, have revealed the heterogeneity of serotonergic neurons at multiple levels, comprising their electrophysiological properties, suggesting the existence of functionally distinct cellular subpopulations. In order to examine in an unbiased manner whether serotonergic neurons of the dorsal raphe nucleus (DRN) are heterogeneous, we used a non-invasive loose-seal cell-attached method to record α1 adrenergic receptor-stimulated spiking of a large sample of neurons in brain slices obtained from transgenic mice lines that express fluorescent marker proteins under the control of serotonergic system-specific Tph2 and Pet-1 promoters. We found wide homogeneous distribution of firing rates, well fitted by a single Gaussian function (r2 = 0.93) and independent of anatomical location (P = 0.45), suggesting that in terms of intrinsic firing properties, serotonergic neurons in the DRN represent a single cellular population. Characterization of the population in terms of spiking regularity was hindered by its dependence on the firing rate. For instance, the coefficient of variation of the interspike intervals (ISI), a common measure of spiking irregularity, is of limited usefulness since it correlates negatively with the firing rate (r = −0.33, P < 0.0001). Nevertheless, the majority of neurons exhibited regular, pacemaker-like activity, with coefficient of variance of the ISI lower than 0.5 in ~97% of cases. Unexpectedly, a small percentage of neurons (~1%) exhibited a particular spiking pattern, characterized by low frequency (~0.02–0.1 Hz) oscillations in the firing rate. Transitions between regular and oscillatory firing were observed, suggesting that the oscillatory firing is an alternative firing pattern of serotonergic neurons.